Komposter Berbasis Limbah Dapur Sebagai Inovasi Lingkungan Pemberdayaan Masyarakat di Desa Sukodono - Arsyad, Rio Rizal; Amanta, Davin; Putri, Priska Duana; Narinda, Chandrita Hikari; Gunawan, Sefulloh; Anggraeni, Kartika; Pratama, M. Naufal Rizky; Azziyati, Irsalina; Batubara, Tegar Imaman Hakiki; Patriani, Widya; Atmojo, Muhammad Eko (Universitas Muhammadiyah Yogyakarta, 2025)
Organic waste is a type of waste that contains high water content and is easily decomposed, which if not managed properly can cause environmental problems such as pollution and the spread of disease. Proper handling of organic waste is very important to maintain environmental cleanliness and health. One way to process organic waste is to make compost, which not only reduces the volume of waste but also provides ecological benefits through the reuse of organic materials as natural fertilizers. This community service activity was carried out in Sukodono Village, Donorojo, Pacitan with an organic waste management program using a composter. The purpose of this activity is to increase knowledge and skills for residents of Sukodono Village in processing organic waste. The activity began with an explanation through socialization of material about organic waste and compost in general. Furthermore, it was continued with practical training that involved participants directly in making compost. The composting process is carried out in a 20 L composter using EM-4 bioactivator. The results obtained from this community service activity are that participants can understand the technique of processing organic waste into compost fertilizer well. With increasing awareness of the importance of environmental sustainability, the use of composters is not only beneficial for individuals but also has a positive impact on society as a whole. Through socialization and training on composting, it is hoped that the community can learn to manage their own organic waste. In addition, this activity also aims to increase public awareness of the importance of environmental sustainability, as well as provide a wider positive impact, both for individuals and society. By managing organic waste independently, the community can reduce the amount of waste produced and at the same time improve the quality of the soil around them